Recovery of Depleted miR-146a in ALS Cortical Astrocytes Reverts Cell Aberrancies and Prevents Paracrine Pathogenicity on Microglia and Motor Neurons - Barbosa, Marta; Gomes, Cátia; Sequeira, Catarina; Gonçalves-Ribeiro, Joana; Pina, Carolina Campos; Carvalho, Luís A.; Moreira, Rui; Vaz, Sandra H.; Vaz, Ana Rita; Brites, Dora (Frontiers in Cell and Developmental Biology, 2021)
Reactive astrocytes in Amyotrophic Lateral Sclerosis (ALS) change their molecular expression pattern and release toxic factors that contribute to neurodegeneration and microglial activation. We and others identified a dysregulated inflammatory miRNA profile in ALS patients and in mice models suggesting that they represent potential targets for therapeutic intervention. Such cellular miRNAs are known to be released into the secretome and to be carried by small extracellular vesicles (sEVs), which may be harmful to recipient cells. Thus, ALS astrocyte secretome may disrupt cell homeostasis and impact on ALS pathogenesis. Previously, we identified a specific aberrant signature in the cortical brain of symptomatic SOD1-G93A (mSOD1) mice, as well as in astrocytes isolated from the same region of 7-day-old mSOD1 mice, with upregulated S100B/HMGB1/Cx43/vimentin and downregulated GFAP. The presence of downregulated miR-146a on both cases suggests that it can be a promising target for modulation in ALS. Here, we upregulated miR-146a with pre-miR-146a, and tested glycoursodeoxycholic acid (GUDCA) and dipeptidyl vinyl sulfone (VS) for their immunoregulatory properties. VS was more effective in restoring astrocytic miR-146a, GFAP, S100B, HMGB1, Cx43, and vimentin levels than GUDCA, which only recovered Cx43 and vimentin mRNA. The miR-146a inhibitor generated typical ALS aberrancies in wild type astrocytes that were abolished by VS. Similarly, pre-miR-146a transfection into the mSOD1 astrocytes abrogated aberrant markers and intracellular Ca2+ overload. Such treatment counteracted miR-146a depletion in sEVs and led to secretome-mediated miR-146a enhancement in NSC-34-motor neurons (MNs) and N9-microglia. Secretome from mSOD1 astrocytes increased early/late apoptosis and FGFR3 mRNA in MNs and microglia, but not when derived from pre-miR-146a or VS-treated cells. These last strategies prevented the impairment of axonal transport and synaptic dynamics by the pathological secretome, while also averted microglia activation through either secretome, or their isolated sEVs. Proteomic analysis of the target cells indicated that pre-miR-146a regulates mitochondria and inflammation via paracrine signaling. We demonstrate that replenishment of miR-146a in mSOD1 cortical astrocytes with pre-miR-146a or by VS abrogates their phenotypic aberrancies and paracrine deleterious consequences to MNs and microglia. These results propose miR-146a as a new causal and emerging therapeutic target for astrocyte pathogenic processes in ALS.